TRAINING ON PROCESSING BANANA STEMS INTO CHIPS: FOOD PRODUCT INNOVATION BASED ON LOCAL POTENTIAL IN HILIAMURI VILLAGE - Opirman Waruwu; Ambelina Henriques De Carvalho (Haga : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve the skills and knowledge of Hiliamuri Village residents, Teluk Dalam District, South Nias Regency, through training on processing banana midribs into chips as a food product innovation based on local potential. The participants consisted of 35 members of the Family Welfare Empowerment (PKK) group of Hiliamuri Village. The method used was a participatory approach including lectures, demonstrations, hands-on practice, and evaluation. The results showed that all participants successfully understood and independently practiced the banana midrib chip-making process, from raw material selection, cutting, soaking, seasoning, frying, to packaging. This activity successfully raised community awareness regarding the economic value of banana midribs previously considered agricultural waste. This training is expected to encourage the growth of sustainable micro-enterprises based on local potential to improve the economic welfare of Hiliamuri Village community.